Pengaruh Pendapatan Debitur, Besar Pinjaman, dan Kebijakan Restrukturisasi Terhadap Tingkat Kelancaran Pengembalian Kredit di Masa Pandemi Covid-19 Pada Lembaga Perkreditan Desa (LPD) Kecamatan Buleleng - Ni Kadek Wiwiek Widhi Asih; Anantawikrama Tungga Atmadja (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This study aims to determine the effect of debtor income, loan size, and restructuring policies on the smooth rate of credit repayment during the Covid-19 pandemic at the Lembaga Perkreditan Desa (LPD) of Buleleng District. This type of research is quantitative research. The population used is all Lembaga Perkreditan Desa (LPD) in Buleleng District. The sampling technique in this study used purposive sampling with a total sample of 65 respondents. Sources of data used are primary data obtained through the distribution of questionnaires. The data were then analyzed using descriptive statistical analysis, instrument testing, classical assumption testing, and hypothesis testing with the help of the SPSS 26 program. The results showed that debtor income and restructuring policies had a positive and significant impact on the smooth rate of loan repayment during the Covid-19 pandemic at Lembaga Perkreditan Desa (LPD). While, the size of the loan has a negative and significant effect on the smooth rate of credit repayment during the Covid-19 pandemic at the Lembaga Perkreditan Desa (LPD) of Buleleng District.